Financial Stress and Digital Debt Behavior: A Systematic Review of Behavioral Finance Evidence - Priadipa, Arimbi (Haka Vyza Media, 2025)
The rapid expansion of digital lending in Indonesia has reshaped household financial behavior, leading to rising financial stress and impulsive borrowing. These patterns cannot be fully explained by classical economic assumptions of rational decision-making. Emerging evidence shows that digital borrowing decisions are strongly influenced by psychological factors, behavioral biases, and technology design that lowers cognitive barriers to credit access. This study conducts a Systematic Literature Review of 42 publications from 2015–2024 to synthesize the relationships among financial stress, behavioral biases, and digital lending mechanisms. The findings reveal that financial stress triggers biases such as present bias, overconfidence, and optimism bias, which in turn drive impulsive borrowing. The fast, frictionless, and instant-approval nature of digital lending amplifies these biases, creating a recurring debt-stress loop that may escalate into a debt spiral. This study contributes a conceptual model integrating psychological and digital factors to explain vulnerability to digital debt and offers policy implications for regulators and fintech providers to design behaviorally informed interventions that can mitigate overborrowing risks